2016
DOI: 10.1080/21505594.2016.1155015
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial blue light inactivation ofCandida albicans:In vitroandin vivostudies

Abstract: Fungal infections are a common cause of morbidity, mortality and cost in critical care populations. The increasing emergence of antimicrobial resistance necessitates the development of new therapeutic approaches for fungal infections. In the present study, we investigated the effectiveness of an innovative approach, antimicrobial blue light (aBL), for inactivation of Candida albicans in vitro and in infected mouse burns. A bioluminescent strain of C. albicans was used. The susceptibilities to aBL (415 nm) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 53 publications
4
75
1
1
Order By: Relevance
“…For P. aeruginosa, when 110 J/cm 2 aBL was delivered, an approximately 7.64-log 10 CFU inactivation was achieved (Dai et al, 2013b). For A. baumannii and C. albicans , over 4-log 10 CFU were inactivated after an exposure of 70 J/cm 2 aBL (Zhang et al, 2016; Zhang et al, 2014). The inactivation curves of the above pathogens approximately followed first-order kinetics (Xiong et al, 1999), a linear relation between the log-transformed cell survival fraction log 10 and the aBL exposure.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…For P. aeruginosa, when 110 J/cm 2 aBL was delivered, an approximately 7.64-log 10 CFU inactivation was achieved (Dai et al, 2013b). For A. baumannii and C. albicans , over 4-log 10 CFU were inactivated after an exposure of 70 J/cm 2 aBL (Zhang et al, 2016; Zhang et al, 2014). The inactivation curves of the above pathogens approximately followed first-order kinetics (Xiong et al, 1999), a linear relation between the log-transformed cell survival fraction log 10 and the aBL exposure.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…Also, the bioluminescence method is a non-invasive technique; therefore, sequential images could be obtained for each sample, allowing statistical analysis without any inter-sample variation. The method is an alternative to traditional in vitro culture methods using paper point sampling and quantitative culture and has been used in different studies to evaluate infections and bacterial reduction in vitro and in animal models (3, 6, 13, 17, 26, 17, 27). …”
Section: Discussionmentioning
confidence: 99%
“…No development of aBL resistance was observed after 10-20 cycles of repeated aBL exposures. 25,27,28 Other studies demonstrated that aBL did not cause significant damages to host cells and did not impair wound healing. 18,26,28,34,39,40 In this issue of Virulence, Fila et al 22 investigated the effectiveness of aBL inactivation of Pseudomonas aeruginosa using a panel of wide types and clinical strains, including multidrug-resistant and extensively drug-resistant strains.…”
mentioning
confidence: 99%
“…44,45 In the studies of our laboratory, we observed via transmission electron microscopy that sublethal exposures of aBL induced cell wall damage in microbes. 27,30 This may enhance the penetration of antibiotics into microbial cells and subsequently potentiate the inactivation of microbes. Another possibility leading to aBL-induced hyper-susceptibility to antibiotics is the oxidative stress-induced under-expression of drug resistance genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation